PERPUSTAKAAN NAGARI SEBAGAI PUSAT INFORMASI KEBUDAYAAN MINANGKABAU - Dian Hasfera (Jurnal IPI (Ikatan Pustakawan Indonesia), 2015)
Perpustakaan Nagari is the institution information based on local content with purpose to collect, mantain, preservation and dissemination indegenous knowledge of Minangkabau society. Perpustakaan Nagari is different from the other libraries because Perpustakaan Nagari are in the Nagari government system based on customs and culture of Minangkabau. Thefunction of Perpustakaan Nagari are: (1) storage; (2) education; (3) information; (4) research;(5) culture; (6) recreation and (7) transformations of indegenous knowledge. The importance of Perpustakaan Nagari became the culture information central of Minangkabau are (1) Perpustakaan Nagari based on Minangkabau culture and exist only in the West Sumatera (2) Pepustakaan Nagari became instituition transformation from oral tradition into a written. The constraints of Perpustakaan Nagari be a central of culture information Minangkabau are (1) Perpustakaan Nagari equated with the village library (2) don't have librarian (3) skill of staf who manage Perpustakaan Nagari notgood (4) participation of community to develod Perpustakaan Nagari is very low.